2018
DOI: 10.1016/j.enpol.2017.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transfer of innovations: South-South learning on village-scale solar power supply between India and Kenya

Abstract: This article presents research on the transfer of sustainable energy innovations between countries of the global South from a socio-technical perspective. The analysis identifies factors important for how a deliberate transfer process may unfold. It is based on monitoring a case of South-South transfer of experiences with village-level solar power supply models from India to Kenya. This research shows that it is not so much stable technical solutions which travel between different spatial and cultural contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…De esta manera, las metodologías presentadas en la Tabla 2 probablemente aportaron elementos clave en la relación tecnología y sociedad, redirigieron procesos deterministas con TA hacia tecnologías socialmente apropiadas, participativas y de inclusión social; como lo atribuyen (Chen, 2018) y (Ulsrud, Rohracher, & Muchunku, 2018a), los cuales resaltan que el éxito de una transferencia o adopción puede relacionarse con el aprendizaje intercultural colectivo, el intercambio de experiencias, la comprensión rigurosa de los hallazgos, la construcción de conciencia social y el ajuste de políticas públicas entorno a una población o gobierno. Asimismo, es importante priorizar en las características propias de los usuarios y establecer un diálogo horizontal entre los ofertantes tecnológicos, las comunidades rurales, los actores locales y académicos (Garrido, Lalouf, & Thomas, 2011;Méndez-Fajardo, Opazo, Romero-Picón, & Pérez-Muzuzu, 2011).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…De esta manera, las metodologías presentadas en la Tabla 2 probablemente aportaron elementos clave en la relación tecnología y sociedad, redirigieron procesos deterministas con TA hacia tecnologías socialmente apropiadas, participativas y de inclusión social; como lo atribuyen (Chen, 2018) y (Ulsrud, Rohracher, & Muchunku, 2018a), los cuales resaltan que el éxito de una transferencia o adopción puede relacionarse con el aprendizaje intercultural colectivo, el intercambio de experiencias, la comprensión rigurosa de los hallazgos, la construcción de conciencia social y el ajuste de políticas públicas entorno a una población o gobierno. Asimismo, es importante priorizar en las características propias de los usuarios y establecer un diálogo horizontal entre los ofertantes tecnológicos, las comunidades rurales, los actores locales y académicos (Garrido, Lalouf, & Thomas, 2011;Méndez-Fajardo, Opazo, Romero-Picón, & Pérez-Muzuzu, 2011).…”
Section: Resultados Y Discusiónunclassified
“…Adicionalmente, los resultados mostraron que el 79,2% de las veces los investigadores utilizaron metodologías cualitativas y mixtas para estudiar las tres variables de mayor frecuencia de citación (transferencia, implementación y evaluación), fomentando la inclusión social desde una perspectiva interdisciplinaria y participativa para la evaluación, el monitoreo y análisis del grado de aceptación, impacto y difusión de las TA dentro de las comunidades rurales; como también lo reportaron (Winkler, Lemke, Ritter, & Lewandowski, 2017) y (Ulsrud, Rohracher, & Muchunku, 2018a), en donde el rol fundamental de la participación comunitaria rural fue impresindible en procesos de TA. Por otro lado, los hallazgos mostraron que probablemente han emergido nuevas variables de estudio en paralelo a los criterios sociales, culturales e institucionales; estas variables con menor frecuencia de citación fueron: enseñanza (Manalo, y otros, 2016), desarrollo inclusivo (Ockwell, Byrne, Hansen, & Haselip, 2018) y transción socioténica (Nasrat, Sadat, & Sapi, 2018).…”
Section: Factores Y Variables De Estudiounclassified
“…In Wales and Scotland, for example, energy cooperative programs have been most successful in networks of closeknit rural communities (Strand, 2018); while in Alaska several regional grids have emerged and utilities have developed systems for supporting regional energy planning and project maintenance across otherwise remote locations (Holdmann et al, 2019). Similarly, in the global south, research has shown the value in community-to-community mentorship for developing renewable energy projects in rural areas and providing a network for knowledge transfer (Ulsrud et al, 2018). Such community-to-community relationships provide support and enable communities to share success stories and lessons learned of energy transition efforts (Cherniak et al, 2015).…”
Section: Sister Communities As Energy Support Networkmentioning
confidence: 99%
“…A systematic analysis was carried out, and the degree of influence of various factors on the core competitiveness of grassroots power supply enterprises was summarized. e researchers believe that financial core competence is the organic combination of core competitiveness and financial management, and the financial management system of grassroots power supply enterprises runs through all aspects of the operation and management of grassroots power supply enterprises [12].…”
Section: Related Workmentioning
confidence: 99%